The influence of the combination of methanolic extract Scurrula atropurpurea (Blume) and Dendrophthoe pentandra on rat liver function and structure - N. Athiroh; N. J. Mubarakati; Yu. Purnomo (Фармакоэкономика, 2024)
Background. Tea mistletoe (Scurrula atropurpurea (Blume)) and mango mistletoe (Dendrophthoe pentandra) have been known as a potential medicine for several diseases.Objective: to investigate the effect of the combination of methanolic extract Scurrula atropurpurea (Blume) and Dendrophthoe pentandra (MESA-DP) on rat liver function and structure using serological and histopathological analysis.Material and methods. This study was experimental during 28 days using 20 rats divided into four groups (Group 1 as a control, while Groups 2, 3, and 4 were given MESA-DP at doses 250, 500, and 1,000 mg/kg of body weight, respectively). The liver histopathological structure was observed using hematoxylin-eosin staining. The liver function assessment included total bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), total protein, albumin, globulin, cholesterol, triglycerides, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels. Data were analyzed using a one-way ANOVA analysis (ANalysis Of VAriance) and performed via SPSS Statistics 17.0 (IBM, USA).Results. The administration of MESA-DP did not show significant differences at all doses for the liver rat function in total bilirubin, SGOT, SGPT, albumin, cholesterol and triglycerides (p>0.05), while globulin, total protein, HDL and LDL showed significant results (p<0.05). The liver histopathological structure showed the number of pyknotic, karyorrhectic and karyolytic cells in rats after MESA-DP administration compared to controls, which grew with increasing dose.Conclusion. The liver function in rats after being exposed to MESA-DP was not affected in terms of total bilirubin, SGOT, SGPT, albumin, cholesterol, and triglyceride levels. However, using MESA-DP increased the necrotic liver cells. It may be beneficial for the liver health of experimental animals taking into account the correct dosage.